Vedolizumab Therapy in Children With Primary Sclerosing Cholangitis: Data From the Pediatric Primary Sclerosing Cholangitis Consortium. Issue 4 (October 2020) - Laborda, Trevor J.; Ricciuto, Amanda; Aumar, Madeleine; Carman, Nicholas; DiGuglielmo, Matthew; Draijer, Laura G.; Furuya, Katryn N.; Gupta, Nitika; Koot, Bart G.P.; Loomes, Kathleen M.; Lytvyak, Ellina; Martinez, Mercedes; et al.
ABSTRACT: Objectives: Most patients with primary sclerosing cholangitis (PSC) also have inflammatory bowel disease (IBD). The liver and colon express MAdCAM-1, a target of lymphocyte homing integrins. Vedolizumab (VDZ) is an α4β7 integrin antibody used to treat IBD. We investigated liver outcomes in children with PSC-IBD treated with VDZ. Methods: Patients were identified within the Pediatric PSC Consortium, a multicenter research registry. Retrospective demographic, phenotypic, biochemical, radiological, histopathologic and IBD data for up to 1 year of VDZ therapy were collected. Liver biochemical and IBD responses were defined as: a 75% or greater reduction in initial γ-glutamyltransferase (GGT), or a GGT that fell to <50 IU/L and improved Mayo endoscopy grade or IBD activity scores after 9 to 12 months. Results: Thirty-seven patients were identified from 19 centers. VDZ was initiated at median age of 16 years [IQR 15–18], 69% were male, 65% had large duct involvement, 19% had (Metavir F3/F4) fibrosis and 59% had ulcerative colitis. Of 32 patients with abnormal GGT at baseline, 22% had a liver biochemical response after 9 to 12 months. For IBD, 32% achieved remission, 30% had a clinical response, and 38% had no response. Final GGT after 9 to 12 months was 51 [IQR 28–71] in IBD patients in remission versus 127 [IQR 63–226] in those with active IBD, ( P  = 0.066). Conclusions: Liver biochemistry worsened over time in IBD unresponsive to VDZ but remained unchanged in IBD patients in remission. VDZ did not improve liver biochemistry in pediatric PSC-IBD. Progressive liver disease may be more common in patients with medically refractory IBD. Abstract : Supplemental Digital Content is available in the text